The Legal Construction of Tax and Excise Crime Management: The Dilemma Between Fiscal Restoration via Administrative Fines and Money Laundering Enforcement - Hasan, Fuad (The Prosecutor Law Review, 2026)
Tax and excise revenues are strategic pillars of the Indonesian state budget (APBN) currently challenged by structured economic crimes. This research addresses the juridical dilemma between achieving fiscal restoration through administrative sanctions under the ultimum remedium principle and the repressive effectiveness of Money Laundering enforcement. Utilizing a qualitative doctrinal research method, the study analyzes the synchronization of policies in handling fiscal offenses. The research findings indicate that administrative sanction instruments often fail to capture the accumulation of illicit wealth or the appreciation of criminal proceeds that exceed the maximum fiscal fines. The study concludes that law enforcement policies in the Tax and Excise sectors must ensure optimal asset recovery efficiency. The application of Anti-Money Laundering measures is crucial to close procedural loopholes, preventing administrative sanction from being perceived merely as a cost of doing business, while firmly upholding the fundamental principle that crime doesn’t pay